HMGB1 and HMGB2 cell-specifically down-regulate the p53- and p73-dependent sequence-specific transactivation from the human Bax gene promoter - Stros, Michal; Ozaki, Toshinori; Bacikova, Alena; Kageyama, Hajime; Nakagawara, Akira (The Journal of biological chemistry, 2002)
The recently cloned gene p73 is a close homologue of p53, which is a crucial tumor suppressor gene for preventing the malignant transformation of cells by inducing cell cycle arrest and apoptosis. Previous reports have shown that architectural DNA-bending/looping chromosomal proteins HMGB1 and HMGB2 (formerly known as HMG1 and HMG2), which function in a number of biological processes including transcription and DNA repair, interact in vitro with p53 and stimulate p53 binding to DNA containing p53 consensus sites. Here, we report that HMGB1 physically interacts with two splicing variants of p73, alpha and beta (pull-down assay), and enhances binding of p73 to specific cognate DNA sites (gel-shift assay). Both HMG box domains of HMGB1, A and B, interact with p73alpha. Association of HMGB1 with p73, like the demonstrated ability of HMGB1 to stimulate p73 binding to different p53-responsive elements, requires the oligomerization region and/or region between DNA-binding domain and oligomerization domain of p73 (residues 312-381). Transient transfections revealed that ectopically expressed or endogenous HMGB1 and HMGB2 (antisense strategy) significantly inhibit in vivo both p73alpha/beta- and p53-dependent transactivation from the Bax gene promoter (and much less from Mdm2 and p21(waf1) promoters) in p53-deficient SAOS-2 cells. In contrast, HMGB1 and HGMB2 stimulate p73- or p53-dependent transactivation in p53-deficient H1299 cells, irrespective of the promoter used. Our results suggest that ubiquitously expressed HMGB1 and HMGB2 have potential to cell- and promoter-specifically down- or up-regulate in vivo transcriptional activity of different members of the p53 family. A possible mechanism of HMGB1-mediated modulation of p73- and p53-dependent transactivation is discussed.
Keywords: aktivace transkripce; Luciferases; Protein Binding; transfekce; down regulace; Sp1 Transcription Factor; glutathiontransferasa; Cell Line; Plasmids; bcl-2-Associated X Protein; Glutathione Transferase; Up-Regulation; protein p73; HMGB2 Protein; Protein Structure, Tertiary; Transfection; terciární struktura proteinů; luciferasy; Tumor Suppressor Proteins; protoonkogenní proteiny c-mdm2; Proto-Oncogene Proteins; Genes, Tumor Suppressor; proteosyntéza; HMGB1 Protein; Protein Biosynthesis; Transcriptional Activation; upregulace; protein HMGB1; jaderné proteiny; promotorové oblasti (genetika); Genes, p53; DNA vazebné proteiny; Proto-Oncogene Proteins c-mdm2; nádorové supresorové proteiny; protein X asociovaný s bcl-2; transkripční faktor Sp1; vazba proteinů; geny p53; Down-Regulation; lidé; alternativní sestřih; Humans; Promoter Regions, Genetic; Tumor Protein p73; plazmidy; buněčné linie; protoonkogenní proteiny c-bcl-2; Proto-Oncogene Proteins c-bcl-2; Alternative Splicing; protein HMGB2; tumor supresorové geny; DNA-Binding Proteins; Nuclear Proteins; protoonkogenní proteiny